Bela, recatada, do lar e clandestina : perspectivas sobre o aborto inseguro - Casali, Gessiane Pereira (2020)
This dissertation investigates and analyzes the unsafe and clandestine abortion in the brazilian society, from the perspective of civil society and the state, through the health-policy for wom-en. The current Brazilian scenario experiences the resurgence of conservatism, reflecting and reinforcing the historical traits of control over women's bodies and their autonomy. The theme of abortion has been crossed by these historical aspects, limiting that the dialogue on this practice is strengthened in the field of women's health and reproductive and sexual rights. This research was guided by the following general objective: to know and analyze the under-standing of civil society and health-policy managers about abortion, as well as their actions, programs and strategies created for the protection of women, in order to contribute with sub-sidies to reinforce the debate in the field of women's health and their rights. The specific ob-jectives are: 1) to know and analyze the position of civil society in the research represented by feminist movements, religious groups and health professional categories about abortion and possible repercussions on women's health and life; 2) to know and analyze the actions, pro-grams and strategies carried out by health policies that address abortion and how they affect women's health and rights; and 3) to elaborate analyzes and reflections that may support the debate promoting new and possible approaches to the theme. The development of this re-search is based on the Critical Dialectic method based on Historical Materialism, which ac-cording to Triviños (1987) allows it to approach coherent and rational explanations in the face of the phenomena that occur in society. The theoretical categories are historicity, totality and contradiction. The study revealed that civil society, with its limits and possibilities, according to its perspectives on abortion has been articulating itself to make the discussion on the theme of unsafe and clandestine abortion, is know that the debate still cross moral, conservative and religious aspects, which implies an understanding of the dimension of abortion in women's social life and their health. Among the strategies to protect women is to inform them about their rights, which includes access to safe abortion when it is in accordance with the cases allowed by brazilian law, health professionals guided by professional ethics to provide quality and humanized care, regardless of whether abortion is illegal or legal, religion, understanding that their role is to welcome women, seeking not contribute to more harm to women's lives. The management of health-policy for state and municipal women, representing the state, has sought to ensure humanized care for women in health services, but predominantly the central focus has been the abortion allowed by brazilian law, since due to illegality makes it difficult new approaches. There’re no strategies for working on unsafe and illegal abortion other than to ensure that women who come to health networks in situations of clandestine abortion are met by the services. As a parameter to understand and measure the reflexes of unsafe and clandestine abortion in women's lives there is only death, alarming to the carelessness about women's lives. Unsafe and clandestine abortion has been punctuated in discussions as an ex-pression of public health, promoting access as a woman's right, considering her autonomy as a social individual, which drives and strengthens the debate, highlighting the importance of decriminalization for the promotion and expansion of care to women's health.